Beautiful darkness / 2 - Garcia, Kami (Beautiful Creatures, 2010)
In a small southern town with a secret world hidden in plain sight, sixteen-year-old Lena, who possesses supernatural powers and faces a life-altering decision, draws away from her true love, Ethan, a mortal with frightening visions.